If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2-3x)=7(x+1)-33
We move all terms to the left:
3(2-3x)-(7(x+1)-33)=0
We add all the numbers together, and all the variables
3(-3x+2)-(7(x+1)-33)=0
We multiply parentheses
-9x-(7(x+1)-33)+6=0
We calculate terms in parentheses: -(7(x+1)-33), so:We get rid of parentheses
7(x+1)-33
We multiply parentheses
7x+7-33
We add all the numbers together, and all the variables
7x-26
Back to the equation:
-(7x-26)
-9x-7x+26+6=0
We add all the numbers together, and all the variables
-16x+32=0
We move all terms containing x to the left, all other terms to the right
-16x=-32
x=-32/-16
x=+2
| 12-2=3x-6 | | 10r−-7r−20r−17r=-20 | | 3.47(2x-4)+9.773x+1.004=5.216-(x-7.112) | | 12x^2(4x-3)=0 | | 2t=8+1/2t-t=11 | | 2r+24/8=2r-18/2 | | x=3/x+2 | | 4/x-4=x | | -7=5(x+2)+8 | | -4x-36=4(3x+3) | | x-25=3(2x-5) | | -9x-9=-3x-63 | | -x-49=2(2x+3) | | x-28=5(4x+2) | | 4(3x-5)-1=-x+5 | | 5x+27=2(x+5)-10 | | 26=2(3x+4) | | 2x-7=2(2x-4)+5 | | -2x-173=124-11x | | 42=2(4x+5) | | 5x-34=2(5x+3) | | 16=4(2x-4) | | 13x–2(X-4)=8x+1 | | 3(5x-3)-1=-4x-29 | | -201-2x=10x+75 | | 3(x-4)-5=2x-26 | | (x-4)-5=2x-26 | | -14x-63=-9x+32 | | -95=6x | | 2x+19=49-3x | | 4=3h-h+2+10 | | 6x-88=13x+171 |